Effects of unilateral, bilateral and combined plyometric jump training on asymmetry of muscular strength and power, and change-of-direction in youth male basketball players - Cao, J.; Xun, S.; Zhang, R.; Zhang, Z. (Journal of Sports Science & Medicine, 2024)
This study aimed to compare the effects of unilateral (UT), bilateral (BT), and combined (UBT) plyometric training on muscular strength, power, and change-of-direction performance in youth male basketball players. Sixty-six male youth basketball players (age: 16.1 ± 0.8 years) participated in this randomized experimental study, which lasted 8 weeks with a training frequency of 2 sessions per week. The UT group performed only single-leg plyometric exercises, while the BT group conducted similar plyometric drills using both feet. The UBT group combined both approaches, performing one session of UT and one session of BT each week. The players were evaluated at baseline and after the 8-week period using a force platform for the unilateral countermovement jump test (UCMJ), isometric squat test (IST), isometric knee flexor strength test (KFS), leg land and hold test (LHT), and 5-0-5 tests. The asymmetry between legs per outcome was measured using the symmetry angle. The UT, BT, and UBT all significantly improved outcomes in the IST, UCMJ, KFS, LHT, and 5-0-5 tests (p < 0.05) following the intervention, with no significant differences among the three methods. However, while UT and UBT significantly reduced asymmetries in the tests (p < 0.05), BT increased asymmetries. Only, the UT group showed significant improvements over the control group in asymmetry measures: IST asymmetry (mean difference: 1.2%, p = 0.049), KFS asymmetry (mean difference: 2.5%, p < 0.001), and LHT asymmetry (mean difference: 1.1%, p = 0.013). While there are no substantial differences among UT, BT, and UBT in terms of improvements in unilateral tests and symmetry levels, UT stands out for its effectiveness in enhancing neuromuscular performance and reducing asymmetries among basketball players compared to the control condition. UT was the only method that showed significant benefits in this context. Strength and conditioning coaches might consider incorporating UT, either alone or alongside BT, to optimize individual limb strength and coordination.